Revenge [compact disc, unabridged] - Patterson, James, 1947-; Holmes, Andrew (Andrew Mark) (Hachette Audio, 2020)
Former SAS soldier David Shelley was part of the most covert operations team in the special forces. Now settling down to civilian life in London, he has plans for a safer and more stable existence. But the shocking death of a young woman Shelley once helped protect puts those plans on hold.